2011
DOI: 10.1038/ncomms1309
|View full text |Cite
|
Sign up to set email alerts
|

α-Mannosidase 2C1 attenuates PTEN function in prostate cancer cells

Abstract: PTEN dephosphorylates the 3-position phosphate of phosphatidylinositol 3,4,5 triphosphate (PIP(3)), thereby inhibiting AKT activation. Although attenuation of PTEN function has a major role in tumourigenesis, the underlying mechanisms remain unclear. Here we show that α-mannosidase 2C1 (MAN2C1) inhibits PTEN function in prostate cancer (PC) cells and is associated with a reduction in PTEN function in primary PC. MAN2C1 activates AKT and promotes the formation of PTEN-positive DU145 cell-derived xenograft tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 55 publications
(89 reference statements)
3
55
0
Order By: Relevance
“…8). Consistent with this result, we found that an N-terminal fragment of Man2C1 did not have anti-apoptotic activity; notably, this fragment was previously shown to be enough to inhibit the PIP3 phosphatase activity of PTEN (20). Currently, the role of PTEN, if any, in inducing apoptosis upon Man2C1 knockdown remains unknown.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…8). Consistent with this result, we found that an N-terminal fragment of Man2C1 did not have anti-apoptotic activity; notably, this fragment was previously shown to be enough to inhibit the PIP3 phosphatase activity of PTEN (20). Currently, the role of PTEN, if any, in inducing apoptosis upon Man2C1 knockdown remains unknown.…”
Section: Discussionsupporting
confidence: 75%
“…Man2C1 was recently identified as a PTEN-binding protein (20). He et al (20) suggest that Man2C1, by binding to PTEN, attenuates PTEN functions; thus, Man2C1 up-regulation could promote tumorigenesis in prostate cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MAN2C1 overexpression promoted tumor growth and metastasis of xenograft tumors in immunocompromised mice. Moreover, up-regulation of MAN2C1 was observed in human prostate cancer cells, where MAN2C1 seemed to attenuate PTEN functions by binding to PTEN (19). Conversely, down-regulation of MAN2C1 induced growth delay or arrest in nasopharyngeal carcinoma cells (41) and led to mitotic arrest and apoptosis in esophageal cancer cells (20).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, this protein seems to promote the tumorigenesis in human prostate cancer cells by activating the AKT pathway as a result of PTEN-negative regulation (19). Moreover, the suppression of MAN2C1 expression resulted in mitotic arrest and apoptosis of esophageal carcinoma cells in vitro (20).…”
mentioning
confidence: 99%